Теория потенциала для задач дифракции в слое между двумя параллельными плоскостями - Подлипенко, Ю.К. (Український математичний журнал, 1993)
We investigate boundary value problems appearing in acoustic wave diffraction due to obstacles in a layer between two parallel planes. By using potential theory, the boundary value problems are reduced to Fredholm integral equation considered on the obstacle boundary. Existence and uniqueness theorems are proved for the obtained Fredholm equations and, hence, for the boundary value problem.